Becoming A Young Farmer Young People's Pathways Into Farming: Canada, China, India and Indonesia - Srinivasan, Sharada (Rethinking Rural,, 2024)
This open access book is based on a multi-country collaborative research project focussing on Canada, China, India, and Indonesia. It responds directly and concretely to concerns about the generational sustainability of smallholder farming worldwide- reflected in the current UN Decade of Family Farming. Drawing on research that asks how (some) young people continue to pursue a (future) livelihood in farming, the book uses the life-course perspective and privileges voices of young farmers to show that movement away from farming such as time spent in education, migration and non-farm work does not exclude eventual farming futures. The book will be of interest to scholars and students of agrarian studies, anthropology, development studies, gender studies, human geography, rural sociology, and youth studies. Sharada Srinivasan is Associate Professor of Development Studies and Canada Research Chair in Gender, Justice and Development at the University of Guelph, Canada. She is the Principal Investigator of the Social Sciences and Humanities Research Council of Canada (SSHRC)-funded research project from which this edited collection has been developed.